Uma jornada de memorias: celebrando conquistas e desafios - Costa, Edilene Martins da (Brasil, 2024)
This final course work aims to present the training memorial and reflections on the supervised internships in education. It is divided into two chapters that are organized as follows: in the first of them I bring narratives from my childhood, with emphasis on my first contact with the school, going through all the basic education teaching modalities, as well as my entry into the University, providing a reflection on my personal, professional and academic trajectory. Later, I will present observation of the supervised internship, exemplifying each stage with the knowledge acquired during theinternships in each topic. The first one refers to Early Childhood Education, where I will address playfulness and its benefits when applied as a teaching method, followed by a discussion on the relevance of the child's transition process to Elementary School, reflecting on the importance of our teachers are prepared to receive these students and finally in the Education Management internship, I will present the basic principles of democratic management in the school environment. Finally, I will conclude with final considerations, discussing my experience throughout this period of training as a professor in academia.